A model to examine farm household trade-offs and synergies with an application to smallholders in Vietnam - Ditzler, L.; Komarek, Adam M.; Chiang, T.W.; Álvarez, S.; Chatterjee, S.A.; Timler, Carl J.; Estrada-Carmona, Natalia; Kennedy, G.; Groot, Jeroen C.J.; Raneri, Jessica Evelyn (Elsevier, 2019)
Farm models have the potential to describe farming systems and livelihoods, identify trade-offs and synergies, and provide ex-ante assessments of agricultural technologies and policies. We developed three new modules related to budget, labor, and human nutrition for the bio-economic whole-farm model ‘FarmDESIGN’. The expanded model positions the farming enterprise within the farm household. We illustrate the model's new capabilities for farm households in two villages in Northwest Vietnam, where we conducted multi-objective optimization to identify options for improving the farm households' current performance on key sustainability and livelihood indicators. Modeling results suggest trade-offs between environmental, economic, and social objectives are common, although not universal. The new modules increase the scope for modeling flows of resources (namely cash, labor, and food) between the farm enterprise and the farm household, as well as beyond the farm gate. This allows conducting modeling explorations, optimization routines, and scenario analyses in farming systems research.